2020
DOI: 10.29259/sijdeb.v4i3.229-240
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Social Reporting (ISR) Disclosure: Financial Performance Factor

Abstract: The development of ISR in Indonesia is still relatively slow. Several previous studies have proven that all the Sharia banks in the research sample have not achieved 100% implementation and disclosure of ISR. This study uses several independent variables, namely company size, profitability, liquidity, leverage, sharia supervisory board, audit committee, board of commisioners. Based on the results of the previous research, there is still a research gap that occurs. This study used a sample of 13 Sharia Commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(15 reference statements)
1
1
0
2
Order By: Relevance
“…This research is consistent with Kurniawati and Yaya (2017); Puspawati et al (2020). They found that the existence of an AC does not affect ISRD.…”
Section: Audit Committee and Isr Disclosuresupporting
confidence: 91%
See 1 more Smart Citation
“…This research is consistent with Kurniawati and Yaya (2017); Puspawati et al (2020). They found that the existence of an AC does not affect ISRD.…”
Section: Audit Committee and Isr Disclosuresupporting
confidence: 91%
“…It can be said that the existence of an audit committee in the company is proven to reduce the number of ISR disclosures. Despite its existence, this AC does not affect the ISRD (Kurniawati and Yaya, 2017;Puspawati et al, 2020). It means that the number of audit committees owned by the company does not affect the number of ISR disclosures.…”
Section: Introductionmentioning
confidence: 98%
“…Bagi seluruh pemangku kepentingan, dewan komisaris dan jajarannya bertugas untuk menjaga agar tata kelola perusahaan yang baik dapat ditegakkan, termasuk tanggung jawab sosial perusahaan (Rivandi & Putra, 2019). Penelitian Hussain et al (2020) sejalan dengan penelitian Mazri et al (2018), Mukhibad & Fitri (2020) dan Puspawati et al (2020) yang menjelaskan bahwa ukuran dewan komisaris berpengaruh positif terhadap pengungkapan ISR.…”
Section: Pendahuluanunclassified
“…Prinsipal harus dapat memperoleh informasi ini melalui komite audit, yang bertanggung jawab atas pemantauan perusahaan, tata kelola perusahaan, dan pelaporan keuangan. Hasil ini selaras dengan penelitian Puspawati et al (2020) dan Hartawati et al (2018) yang menemukan bahwa pengungkapan ISR tidak dipengaruhi komite audit.…”
Section: Pengaruh Komite Audit Terhadap Pengungkapan Isrunclassified